(untitled) (Journal of Life and Earth Science, 2012)
This study shows that enhancement of soil fertility along with the yield of chickpea due to nodulation by the Rhizobium is possible to some extent. Data on plant height (cm) at maturity, primary branches/plant, days to flower, pods/plant, pod dry weight/plant (g), seeds/pod, seed dry weight/pod (g), 50 seeds weight (g), nodules/plant, fresh weight of nodules/plant and dry weight of nodules/plant were considered to assess the effect of nodulation in chickpea. Soils treated with Rhizobium always showed higher values than control regarding total nitrogen and organic matter (%). Campus soil showed the highest value for organic matter (%) and N content but Cholonbil soil exhibited the highest value for number of seeds per pod. All the parameters for growth analysis yielded greater values for treated soils compared to that of the control. DOI: http://dx.doi.org/10.3329/jles.v6i0.9720 JLES 2011 6: 45-50